Restriction factors in human retrovirus infections and the unprecedented case of CIITA as link of intrinsic and adaptive immunity against HTLV-1 - Forlani, Greta (Retrovirology, 2019)
BACKGROUND: Immunity against pathogens evolved through complex mechanisms that only for sake of simplicity are defined as innate immunity and adaptive immunity. Indeed innate and adaptive immunity are strongly intertwined each other during evolution. The complexity is further increased by intrinsic mechanisms of immunity that rely on the action of intracellular molecules defined as restriction factors (RFs) that, particularly in virus infections, counteract the action of pathogen gene products acting at different steps of virus life cycle. MAIN BODY AND CONCLUSION: Here we provide an overview on the nature and the mode of action of restriction factors involved in retrovirus infection, particularly Human T Leukemia/Lymphoma Virus 1 (HTLV-1) infection. As it has been extensively studied by our group, special emphasis is given to the involvement of the MHC class II transactivator CIITA discovered in our laboratory as regulator of adaptive immunity and subsequently as restriction factor against HIV-1 and HTLV-1, a unique example of dual function linking adaptive and intrinsic immunity during evolution. We describe the multiple molecular mechanisms through which CIITA exerts its restriction on retroviruses. Of relevance, we review the unprecedented findings pointing to a concerted action of several restriction factors such as CIITA, TRIM22 and TRIM19/PML in synergizing against retroviral replication. Finally, as CIITA profoundly affects HTLV-1 replication by interacting and inhibiting the function of HTLV-1 Tax-1 molecule, the major viral product associated to the virus oncogenicity, we also put forward the hypothesis of CIITA as counteractor of HTLV-1-mediated cancer initiation.